Characterization of Gafchromic HD-V2 Film for dose verification in stereotactic radiosurgery (SRS) / Muhammad Taufiq Azman - Muhammad Taufiq, Azman (2018)
The purpose of this study was to characterize specific dosimetric properties of Gafchromic HD-V2 film and to investigate its feasibility in the dosimetric verification for Stereotactic Radiosurgery (SRS). Basic dosimeter properties including energy and dose rate dependencies were investigated and HD-V2 film showed energy and dose rate dependencies of less than 9.5% and 4.94% respectively. The HD-V2 film has very low dependency on scanning orientation in portrait versus landscape as well as “face-up” versus “face-down” scanning orientation. The percentage differences recorded were less than 2.7% for portrait versus landscape and less than 2.5% for “face-up” versus “facedown” orientation. In terms of angular dependency, there was no significant influence on net optical density, with deviations less than 4.3% for films irradiated at selected gantry angles ranging from 0° (which film is perpendicular to the irradiation beam) to 180°. Two treatment plans using SRS technique were created and irradiated using HD-V2 film for dosimetric verification. The dose distributions were calculated using a treatment planning system to obtain point doses at specified positions within a phantom. The calculated doses from TPS were compared to dose distributions delivered to HD-V2 film. The results of the point dose measurements for SRS treatment irradiations showed that the deviations between the TPS predicted dose and HD-V2 film measurements were less 4% which were within the recommended values by ICRU. This study shows that Gafchromic HD-V2 film can be used as dosimetric verification for SRS and for radiotherapy clinical practices that involves high range of doses of 10 to 1000 Gy